(untitled) (Research, Society and Development, 2021)
Brazil is among the countries with the highest biological biodiversity in the world, estimated at 20% of the species already known as a whole. The fungi comprise a heterogeneous group of microorganisms, being able to be sapróbios, parasites or symbionts. Often the elements of diversity less visible are considered to be the most important for maintaining life. These microorganisms are extremely important in the production of products that are used in the pharmaceutical industries, being a source of substance in the fight against infectious diseases. The aim of this research was to evaluate the antimicrobial activity of isolated soil fungi on Staphylococcus aureus. The fungi were collected in the Municipality of Iranduba, transported to the multidisciplinary laboratory of the Superior Baptist School of Amazonas - Esbam, where they were isolated, purified and preserved in 20% Glycerol. F4 and F9 were separated for the test. In the antimicrobial activity test, only the F4 species developed a inhibition halo of 0.9mm.